x2-11x+12=0

Simple and best practice solution for x2-11x+12=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2-11x+12=0 equation:



x2-11x+12=0
We add all the numbers together, and all the variables
x^2-11x+12=0
a = 1; b = -11; c = +12;
Δ = b2-4ac
Δ = -112-4·1·12
Δ = 73
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-\sqrt{73}}{2*1}=\frac{11-\sqrt{73}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+\sqrt{73}}{2*1}=\frac{11+\sqrt{73}}{2} $

See similar equations:

| 101.47=$0.14x+$3.47 | | .067=(40.304x)-(302.7852x) | | 6x-(3x+10)=5 | | 10-(-6-8b)=0 | | 7x+3=2(x-5) | | -19x+76=-140-15x | | 16-8b=0 | | 5/4r+30=-30 | | -17x143=-116-10x | | 16x2-16=0 | | (4x+68)-(15x-35)=-40 | | x=15-2√x | | 6/5r+36=-36 | | 199+49+79m=880 | | 2(27-b)=100-4b=6(3-b) | | -5+2(x-1)=-12+2x | | 40x-4.5=112 | | Xx3+xx12=30 | | 3=-5/6+w | | 2y-3=18-y | | -5x+2(x-1)=12+2x | | 9x-9=67 | | 7.2a+11=97.4 | | 5-4/k-1/k2=0 | | 5x-4=0.2(5+20x) | | -354=-6x+6(-2x-41) | | 2-1/2x^2=0 | | F(x)=√(5x-20) | | n(n-3)/2=9 | | 9x+15=-9x-17 | | 9x+15=-9x- | | x/6+15=0 |

Equations solver categories